Hypertensive coronary microvascular dysfunction: a subclinical marker of end organ damage and heart failure. (28th March 2020) - Zhou, Wunan; Brown, Jenifer M; Bajaj, Navkaranbir S; Chandra, Alvin; Divakaran, Sanjay; Weber, Brittany; Bibbo, Courtney F; Hainer, Jon; Taqueti, Viviany R; Dorbala, Sharmila; Blankstein, Ron; Adler, Dale; et al.
Abstract: Aims: Hypertension is a well-established heart failure (HF) risk factor, especially in the context of adverse left ventricular (LV) remodelling. We aimed to use myocardial flow reserve (MFR) and global longitudinal strain (GLS), markers of subclinical microvascular and myocardial dysfunction, to refine hypertensive HF risk assessment. Methods and results: Consecutive patients undergoing symptom-prompted stress cardiac positron emission tomography (PET)-computed tomography and transthoracic echocardiogram within 90 days without reduced left ventricular ejection fraction (<40%) or flow-limiting coronary artery disease (summed stress score ≥ 3) were included. Global MFR was quantified by PET, and echocardiograms were retrospectively analysed for cardiac structure and function. Patients were followed over a median 8.75 (Q1–3 4.56–10.04) years for HF hospitalization and a composite of death, HF hospitalization, MI, or stroke. Of 194 patients, 155 had adaptive LV remodelling while 39 had maladaptive remodelling, which was associated with lower MFR and impaired GLS. Across the remodelling spectrum, diastolic parameters, GLS, and N-terminal pro-B-type natriuretic peptide were independently associated with MFR. Maladaptive LV remodelling was associated with increased adjusted incidence of HF hospitalization and death. Importantly, the combination of abnormal MFR and GLS was associated with a higher rate of HF hospitalization compared to normal MFR and GLS [adjusted hazard ratio (HR) 3.21, 95% confidence interval (CI) 1.09–9.45, P = 0.034), including in the adaptive remodelling subset (adjusted HR 3.93, 95% CI 1.14–13.56, P = 0.030). Conclusion: We have demonstrated important associations between coronary microvascular dysfunction and myocardial mechanics that refine disease characterization and HF risk assessment of patients with hypertension based on subclinical target organ injury.